Effect of Dissolution Temperature on Purity of LaNi5 Powder Synthesized with the Combustion-Reduction Method - Ade Utami Hapsari; Retna Deca Pravitasari; Hanif Yuliani; Damisih Damisih; Deni Shidqi Khaerudini; Aghni Ulma Saudi; Jarot Raharjo (Journal of Engineering and Technological Sciences, 2021)
The LaNi5 intermetallic phase has been extensively investigated because of its excellent properties, such as attractive hydrogen storage, medium plateau pressure, and easy activation. LaNi5 phase is generally produced by a complicated method, which involves several steps, i.e. melting, alloying, casting, softening and making them into powder. This study aimed to develop a new LaNi5 synthesis process by modifying the combustion-reduction method. In this method it is very important to produce La2NiO4, because LaNi5 is formed from the process of reducing this phase. The precursor powders La(NO3)3.6H2O and Ni(NO3)2.6H2O were reacted with distilled water as a solvent medium and mixed using magnetic stirring. The synthesis process was carried out at room temperature, 60 °C, 70 °C, and 80 °C for 10 minutes until the solution became transparent green. The solution was then dried for 2 hours at 100 °C to form a transparent green gel. The gel was calcined at a temperature of 500 °C for 2 hours, producing a black powder. The optimal black powder was then reduced using CO gas at 600 °C for 2 hours. The powder samples were characterized using XRD, FTIR, and SEM-EDX. The analysis revealed that synthesis at room temperature was the most optimal method for the reduction process because it produced the most La2NiO4, at 12.135 wt%.